STRATEGI PENGUATAN PENDIDIKAN KARAKTER SISWA MADRASAH IBTIDAIYAH DI ERA DIGITAL: SYSTEMATIC LITERATURE REVIEW - Nugrahaeni, Nugrahaeni Putri Purnomo; Arjuna Fatwa Alghifari; Hanum Nur Faizah; Setiorini Rahma Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education in the digital era has become a serious challenge for educational institutions, particularly Islamic elementary schools (Madrasah Ibtidaiyah/MI). This study aims to identify and analyze various strategies for strengthening character education among MI students in the digital era through a Systematic Literature Review (SLR) approach. Article selection followed the PRISMA 2020 guidelines, with searches conducted across Google Scholar, Sinta, and Scopus databases using relevant keywords. Of the 90 articles initially identified, 17 met the inclusion criteria and were used as the primary sources of analysis. The findings indicate that the most effective strategies include habituation of Islamic and national values, teacher role modeling, integration of character into the curriculum, and strengthening of morality-based digital literacy. MI holds a distinct advantage in fostering religious character, as its curriculum contains a greater proportion of integrated Islamic studies. Furthermore, the role of the principal, parental involvement, and a supportive school environment are key factors in the success of character education programs. This study concludes that strengthening the character of MI students in the digital era requires a holistic approach that engages the entire educational ecosystem, not merely classroom instruction.